Penilaian Bisnis dan Prediksi Kebangkrutan Perusahaan: Studi pada Emiten Yang Listing pada Papan Akselerasi Bursa Efek Indonesia - Agung Prabowo; Yansyah, Deli (LPPM ITK, 2023)
Business valuation is one of the fundamental aspecs that must be done in making investment decisions and to evaluate company performance. The risk of bankruptcy is a risk that always exists in business, so it is important to mitigate. This research try to determine the value of the company using financial ratio analysis, which consists of liquidity, solvency, activity, and profitability ratios. Furthermore, bankruptcy prediction analysis is also carried out to determine the possibility of the company experiencing bankruptcy. we observed two companies in the transportation and logistics sector that are listed on the acceleration board, PT. Prima Globalindo Logistik, Tbk (Ticker Code: PPGL) and PT. Utama Radar Cahaya, Tbk (Ticker Code: RCCC). The results show that two companies have good financial ratios and a low risk of bankruptcy